1988
DOI: 10.1128/jb.170.1.184-189.1988
|View full text |Cite
|
Sign up to set email alerts
|

Dicarboxylic acid transport in Bradyrhizobium japonicum: use of Rhizobium meliloti dct gene(s) to enhance nitrogen fixation

Abstract: Arch. Microbiol. 144:142-146, 1986) was used to study the relationship between dicarboxylic acid transport and nitrogen fixation in Bradyrhizobium japonicum. The expression of the dct sequences on plasmid pRK290:4:46 in B. japonicum CJ1 resulted in increased growth rates in media containing dicarboxyiic acids as the sole source of carbon. In addition, strain CJl(pRK290:4:46) exhibited enhanced succinate uptake activity when grown on dicarboxylic acids under aerobic conditions. Under free-living nitrogen-fixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Better performing Rhizobium strains, at least under laboratory conditions, are being constructed by different methods (Evans et al, 1987;Birkenhead et al, 1988;Cannon et al, 1988;Paau, 1989;Sober6n et al, 1989; 0735-2689/97/$.50 Spaink et al, 1989;Bosworth et al, 1994;Sharypova et al, 1994). However, until solutions to the nodule occupancy problem are found, these advances will be of limited agronomical benefit.…”
Section: Documentation Of the Problemmentioning
confidence: 97%
“…Better performing Rhizobium strains, at least under laboratory conditions, are being constructed by different methods (Evans et al, 1987;Birkenhead et al, 1988;Cannon et al, 1988;Paau, 1989;Sober6n et al, 1989; 0735-2689/97/$.50 Spaink et al, 1989;Bosworth et al, 1994;Sharypova et al, 1994). However, until solutions to the nodule occupancy problem are found, these advances will be of limited agronomical benefit.…”
Section: Documentation Of the Problemmentioning
confidence: 97%
“…To our knowledge, Pps and Pck are the only examples of suboptimally produced enzymes in central metabolism, other than transport proteins such as LacY in E. coli (10) and the dicarboxylic acid transport protein (d/ct gene product) in Bradyrhizobilni japonicium (2). Other studies have shown that the wild-type levels of 3-galactosidase, GltA, and enzyme III ' of the phosphotransferase system are optimal for E. coli growth on lactose (8), acetate (28), and on glucose (25), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest in this report a simple procedure for separating passive and active uptake rates, and we document the importance of accounting for CO, evolution. Rhizobium meliloc dct gene(s) to Bradyrhizobium japonicum Materials and methods enhanced nitrogen fixation (Birkenhead et al 1988 For personal use only.…”
Section: Introductionmentioning
confidence: 99%